A Contrastive Analysis of Cultural Transfer Errors Found in the Harry Potter Movie Dialogues - Siregar , Ayu Juniaty; Hawa, Pratiwi; Wulandari, Siti Zahara; Ritonga, Lingga Sahara; Fahriza, Icha; Ismahani, Siti (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2025)
This study investigates cultural transfer errors in the dialogues of the Harry Potter film series within the context of English as a Foreign Language (EFL) learning. Based on contrastive and error analyses, this study aims to identify types of cultural transfer errors and explain how differences in cultural and pragmatic norms between first (L1) and second (L2) languages contribute to learners’ misinterpretation of meaning. Using a descriptive qualitative method, data were collected from selected film dialogues containing idiomatic expressions, politeness strategies, and culturally embedded meanings. The findings reveal that EFL learners tend to interpret idiomatic expressions literally, resulting in the loss of emotional, evaluative, and pragmatic meanings intended by the speaker. These errors are primarily caused by L1 interference and limited cultural awareness, particularly regarding indirectness and idiomatic language use in English. The study concludes that cultural transfer errors extend beyond grammatical inaccuracies and significantly affect pragmatic competence. The study underscores the importance of incorporating cultural and pragmatic instruction into EFL learning and showcases the efficacy of film dialogue as authentic material for cultivating learners' cross-cultural communicative competence.